Being Vulnerable, Being (In)Dependent: Understanding Liminality Experiences of the Elderly in Central Java, Indonesia - Windarti, Yayuk (Studi Budaya Nusantara, 2026)
A number of studies have examined elderly care, yet most narratives tend to position older people as dependent on their families, particularly their children. Such perspectives often overlook the complexity of lived experiences, as well as the challenges and adaptive strategies that the elderly develop in navigating vulnerability. This paper therefore addresses three main questions: how do the elderly transform and endure conditions of vulnerability? To what extent can they rely on their children? And what happens when such dependency is no longer possible? This research explores the experiences of elderly people in Gotong Village, Central Java, focusing on the dynamics of care and life transitions. The analysis draws on Viktor Turner’s concept of liminality, which outlines three phases of transition: preliminal, liminal, and postliminal. The findings show that the preliminal phase is marked by a disengagement from previous social roles and relationships. During the liminal phase, the elderly experience ambiguity, including unclear social roles, ongoing negotiation between formal and informal care, and uncertainty about the future. This phase highlights how the elderly are not only vulnerable but also actively navigating and making sense of their changing circumstances. In the postliminal phase, they enter a stage of reaggregation under new conditions, often shaped by cultural values, particularly notions of self-acceptance. Overall, the experiences of the elderly should not be understood solely in terms of dependency, but as dynamic processes involving negotiation, adaptation, and meaning-making in the face of vulnerability. Keywords: elderly, vulnerable, liminal, care, dependency